Impact of salt bridges on the equilibrium binding and adhesion of human CD2 and CD58. - Bayas, M; Kearney, A; Avramovic, A; Van Der Merwe, P; Leckband, D (2007)
This study describes quantitative investigations of the impact of single charge mutations on equilibrium binding, kinetics, and the adhesion strength of the CD2-CD58 interaction. Previously steered molecular dynamics simulations guided the selection of the charge mutants investigated, which include the CD2 mutants D31A, K41A, K51A, and K91A. This set includes mutations in which the previous cell aggregation and binding data either agreed or disagreed with the steered molecular dynamics predictions. Surface plasmon resonance measurements quantified the solution binding properties. Adhesion was quantified with the surface force apparatus, which was used previously to study the closely related CD2-CD48 interaction. The results reveal roles that these salt bridges play in equilibrium binding and adhesion. We discuss both the molecular basis of this behavior and its implications for cell adhesion.